Berber - Souag, Lameen (My University, 2020)
Arabic has influenced Berber at all levels – not just lexically, but phonologically, morphologically, and syntactically – to an extent varying from region to region. Arabic influence is especially prominent in smaller northern and eastern varieties, but is substantial even in the largest varieties; only in Tuareg has Arabic influence remained relatively limited. This situation is the result of a long history of large-scale asymmetrical bilingualism often accompanied by language shift.
Keywords: berber; HUMANITIES and RELIGION::Languages and linguistics::Other languages::Arabic language; asymmetrical bilingualism